Simple and Sensitive Electrochemical DNA Detection of Primer Generation‐Rolling Circle Amplification. Issue 5 (4th March 2013) - Lee, Derek Chun; Yip, Shea Ping; Lee, Thomas M. H.
Abstract A new electrochemical sequence‐specific DNA detection platform based on primer generation‐rolling circle amplification (PG‐RCA), methylene blue (MB) redox indicator, and indium tin oxide (ITO) electrode is reported. In the presence of a specific target sequence, PG‐RCA, an isothermal DNA amplification technique, produced large amounts of amplicons in an exponential manner. In addition to the standard components, the reaction mixture contained MB, which bound with the PG‐RCA amplicons. End‐point electrochemical measurement by differential pulse voltammetry (DPV) was performed using ITO electrode. The amplicon‐bound MB resulted in a lower DPV signal than free MB due to a smaller diffusion coefficient as well as electrostatic repulsion between the negatively charged amplicon‐bound MB and ITO electrode. With simple assay design (recognition probe) and instrumentation (operating temperature at 37 °C and ITO electrode without the need for probe immobilization), this detection platform is well suited for point‐of‐care and on‐site testing. Real‐time measurement was also achieved by pretreating the ITO electrode with bovine serum albumin.